Analisa Hukum terhadap Pemegang Hak Cipta dalam Ganti Rugi Pembayaran Royalti - Nurul Ramadhini; Kartika Dewi Irianto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Copyright infringement in the music sector continues to be a significant issue in Indonesia, particularly when musical works are commercially used by business operators. Copyright law provides legal protection for creative works, including songs or music, by granting exclusive rights to control use and derive benefits from such creations. This research examines the legal analysis of copyright holders in compensation for royalty payments. The method used in this research is normative, supplemented by literature studies, including relevant regulations and previous research on song or music copyright. The research findings indicate that royalty payment is a legal obligation for every user of songs in commercial activities, and creators are entitled to such compensation. However, in the Mie Gacoan case in Bali, it is evident that the implementation of these provisions remains constrained due to weak legal understanding, supervision, and compliance, necessitating strengthened law enforcement and optimization of the role of collective management institutions.